Perspective on Terahertz Applications in Bioscience and Biotechnology - Markelz, A. G.; Mittleman, D. M. (ACS Photonics, 2022)
Within the field of terahertz science and technology, one of the most active areas of current research focuses on the intersection of terahertz measurements and methods with the world of biology and medicine. Current activities revolve around numerous diverse questions, ranging from studies of the vibrational spectra of biomolecules and macromolecular complexes to biosensing to medical diagnostics based on noninvasive imaging techniques. Unlike many other areas in which terahertz science is now making inroads, this research domain has been plagued with a number of misleading ideas, which originated at least two decades ago and continue to crop up in current literature. In the worst case, these unfortunate notions can distract from, and even obscure, fascinating and meaningful results. The purpose of this Perspective is to highlight a few of these mistaken concepts and, more importantly, to distinguish them from the many interesting works that continue to emerge from the fruitful marriage of terahertz with biology and medicine.